Asociación entre la contaminación del aire y la morbilidad por Enfermedad Respiratoria Aguda en menores de 5 años en tres localidades de Bogotá (2010)
Abstract. In Bogotá the largest air pollutant is particulate matter smaller than 10 microns (PM lO). Children under 5 spend most of the day inside the kindergarten and are exposed to this pollutant emitted from various pollution sources. The sample of 619 children, of whom 315 lived in area considered of greatest exposure to PM10 and 304 in the lowest exposure, exhibiting a mean difference of PM intramural between higher and lower exposure vs 85.6 I-lg/m 3 . 61 .8 I-lg/m3 (P0.05). Were followed at upper and lower respiratory symptoms for 119 days. The proportion of infants with wheezing in the last year was 74.3%. By far the greater and lesser exposure of 79.6% vs 69.0% (p 0.05). Symptoms of wheeze and cough were associated with increased exposure to PM10 (RR 1.39 and 1.30). A child under 5 years exposure to PM10 presented 1.70 times greater risk of school absenteeism for acute respiratory illness. A decrease of PMlO reduced by 41 .1 % this symptom. The other factors associated with respiratory symptoms were a history of low birth weight and having previously submitted wheezing. Also identified as factors associated with passive smoking (RR 1.5), the proximity of the garden or home within 100 meters of chimneys and roads in poor condition (RR 1.09) , high-way traffic flow (RR 1,85) and co-sleeping (RR 1.92) P 0.05.